2012
DOI: 10.1128/jcm.01730-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Statistical Methods for Establishing Tentative Wild-Type Population and Epidemiological Cutoff Values for Echinocandins, Amphotericin B, Flucytosine, and Six Candida Species as Determined by the Colorimetric Sensititre YeastOne Method

Abstract: The Sensititre YeastOne (SYO) method is a widely used method to determine the susceptibility of Candida spp. to antifungal agents. CLSI clinical breakpoints (CBP) have been reported for antifungals, but not using this method. In the absence of CBP, epidemiological cutoff values (ECVs) are useful to separate wild-type (WT) isolates (those without mechanisms of resistance) from non-WT isolates (those that can harbor some resistance mechanisms), which is the goal of any susceptibility test. The ECVs for five agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 26 publications
1
44
1
Order By: Relevance
“…The MIC ranges of voriconazole and posaconazole among C. tropicalis isolates (n ϭ 98) were 0.03 to Ͼ8 g/ml (MIC 90 , 0.25 g/ml) and 0.06 to Ͼ8 g/ml (MIC 90 , 0.5 g/ml). These findings contrast greatly with previous reports (12,15). The MIC 90 s of voriconazole and posaconazole in the present study were 4-fold higher than those reported by Pfaller et al, who demonstrated that the MICs of voriconazole and posaconazole among C. tropicalis isolates (n ϭ 1,895) ranged from 0.007 g/ml to 4 g/ml (MIC 90 , 0.06 g/ml) and from 0.007 g/ml to 2 g/ml (MIC 90 , 0.12 g/ml), respectively (14).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…The MIC ranges of voriconazole and posaconazole among C. tropicalis isolates (n ϭ 98) were 0.03 to Ͼ8 g/ml (MIC 90 , 0.25 g/ml) and 0.06 to Ͼ8 g/ml (MIC 90 , 0.5 g/ml). These findings contrast greatly with previous reports (12,15). The MIC 90 s of voriconazole and posaconazole in the present study were 4-fold higher than those reported by Pfaller et al, who demonstrated that the MICs of voriconazole and posaconazole among C. tropicalis isolates (n ϭ 1,895) ranged from 0.007 g/ml to 4 g/ml (MIC 90 , 0.06 g/ml) and from 0.007 g/ml to 2 g/ml (MIC 90 , 0.12 g/ml), respectively (14).…”
Section: Discussioncontrasting
confidence: 57%
“…Although the agreement of the SYO method and reference CLSI method with 24-h MICs was reported to be 95% to 99% for all Candida species and antifungal agents (8)(9)(10), these methods may fail to give identical results on certain occasions (8,9). The epidemiological cutoff values determined by the 24-h SYO method differ by within one dilution from those determined by the 24-h CLSI BMD method (12). This might limit the use of CLSI breakpoints for interpretation of the results obtained by the SYO method.…”
Section: Recently Eschenauer Et Al Have Demonstrated That Use Of Syomentioning
confidence: 77%
See 2 more Smart Citations
“…The remaining 17 isolates belonged to those Candida species (e.g., C. kefyr, C. pelliculosa) for which amphotericin B or flucytosine ECVs were not defined (29). Tentative ECVs for the SYO method were recently proposed, and the median values obtained by the five approaches employed for flucytosine and C. albicans, C. parapsilosis, and C. tropicalis were almost identical to those obtained with the CLSI method (41). For these species, the MIC ranges of flucytosine obtained in the present study were similar to those obtained in two earlier surveys, both of which used the SYO method (20,40), but a higher proportion of our C. parapsilosis complex or C. tropicalis isolates exhibited flucytosine MICs greater than the CLSI ECVs.…”
Section: Resultsmentioning
confidence: 92%